A Hebrew Exegesis of Isaiah 62:6-9 The Affirmation of Zion’s Future Blessings - Philip Suciadi Chia; Juanda Juanda (Theological Journal Kerugma, 2020)
The book of Isaiah is really interesting to explore. Many conflicts occurred there, both in relation to God and with other nations. In this study, spiritual, social-ethic and political background will be scrutinized to assist to understand Isaiah chapter 62 comprehensively. Spiritual life of God’s people is declined in the book of Isaiah because of idolatries and nations. Hebrew people make idols out of trees and worship pagan wooden idols (40:18-20; 44:9-20). Not only will God give to His redeemed Zion all that is necessary but in addition, He will appoint watchmen upon her walls that she may receive the utmost in protection. It is clear Isaiah is not exclusively interested in the interpersonal and social relationship structures within Israel. He is also concerned with the broader canvas of international politics. During Isaiah ministry, it was a time of great political turmoil for the nation of Judah because facing the opposition that coming from the north and east.